A closer look at the frame-of-reference effect in personality scale scores and validity - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2008)
This article contributes to the understanding of why the use of a frame-of-reference leads to increased criterion-related validity of personality inventories. Two competing explanations are described and tested. A between-subjects (N = 337) and a within-subject (N = 105) study are conducted to test the hypothesized effects of use of a frame of reference on reliability and validity. Regarding the effects on reliability, use of a frame of reference reduces within-person inconsistency (instead of between-person variability) in responding to generic items. Use of a frame of reference further leads to higher validity as a result of the reduction of between-person variability and within-person inconsistency. Yet, reducing these inconsistencies is not enough. It is also important to use a frame of reference that is conceptually relevant to the criterion. Besides implications for contextualized personality inventories, these results provide an explanation for the moderate validities of generic personality inventories.